Approximate Near-Real-Time Assessment of Some Characteristic Parameters of the Spring Ozone Depletion over Antarctica Using Ground-Based Measurements - Boyan H. Petkov; Vito Vitale; Piero Di Carlo; Héctor A. Ochoa; Adriana Gulisano; Iona L. Coronato; Kamil Láska; Ivan Kostadinov; Angelo Lupi; Mauro Mazzola; Alice Cavaliere; Claudia Frangipani; et al. (Remote Sensing, 2025)
The strong Antarctic vortex plays a crucial role in forming an expansive region with significant stratospheric ozone depletion during austral spring, commonly referred to as the Antarctic “ozone hole”. This study examines daily ozone column behavior during this phenomenon using ERA5 reanalysis data and ground-based observations from 10 Antarctic stations collected between September and December from 2008 to 2022. A preliminary analysis of these datasets revealed smoothly varying patterns with quasi-uniform gradients in the ozone distribution within the ozone hole. This observation led to the hypothesis that average ozone columns over zones, defined as concentric areas around the South Pole, can be estimated using mean values of the measurements derived from station observations. This study aims to evaluate the validity of this hypothesis. The results indicate that the mean ozone levels calculated from daily measurements at two stations—Belgrano and Dome Concordia, or Belgrano and Arrival Heights—provide a reliable approximation of the average ozone levels over the zone spanning 70°S to 90°S. Including additional stations extended the zone of reliable approximation northward to 58°S. The approximation error was estimated to range from 5% to 7% at 1σ and from 6% to 8% at the 10th–90th percentile levels. Furthermore, the geographical distribution of the stations enabled a schematic reconstruction of the ozone hole’s position and shape. On the other hand, the high frequency of ground-based measurements contributed to studying the ozone hole variability in both the inner area and edges on an hourly time scale. These findings have practical implications for the near-real-time monitoring of ozone hole development, along with satellite observations, considering ground-based measurements as a source of information about ozone layer in the South Pole region. The results also suggest the possible role of observations from the ground in the analyses of pre-satellite-era hole behavior. Additionally, this study found a high ...